Corporate Governance Responses to Director Rule Changes - Kay, Benjamin S.; Vojtech, Cindy M. (Journal of Leadership, Accountability and Ethics, 2016)
U.S. stock exchanges and the Sarbanes–Oxley Act mandated minimum standards of director independence to mitigate agency problems. The consequences are studied using a new dataset with a much larger range of firm size. Firms most treated by the director rules decrease CEO stock ownership (6 percent) and decrease the share of stock compensation (30–60 percent). The average treated firm also added two interlocking directorships. Additionally, the rules failed to reduce CEO misbehavior like excess compensation or low turnover. Because treated firms do not outperform the market, these results are more consistent with governance reoptimization than governance improvement.